2016
DOI: 10.1002/slct.201600122
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Silver and Gold Nanoparticles in a Metal-Free Phthalocyanine Liquid Crystalline Matrix: Structural, Thermal, Electrical and Nonlinear Optical Characterization

Abstract: The properties of self-assembled supramolecular structures change remarkably upon the dispersion of a minute amount of metal nanoparticles in them. Here we present, for the first time, investigations of the effect of dispersing alkyl thiol functionalized group-XI metal nanoparticles (silver and gold) in a phthalocyanine-based discotic liquid crystal on their structural, electrical, thermal and nonlinear optical transmission properties, and supramolecular order. Results indicate uniform dispersion of about 0.5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…107 High EQE of 470% in the Q-band absorption region of C6PcH2 and a high energy-conversion efficiency of 3.1% were achieved with different compositions of both donor and acceptor materials. The values of V OC is 0.81 V, I SC of 9.6 mA cm − 2 and FF of 40% were observed for the solar cell with the C6PcH2:PC 61 BM composite layer at a weight ratio of 2:1. To improve the FF of the above device, they studied the optimization of the active layer thickness and insertion of buffer layer.…”
Section: Liquid Crystals In Photovoltaics M Kumar and S Kumarmentioning
confidence: 86%
See 2 more Smart Citations
“…107 High EQE of 470% in the Q-band absorption region of C6PcH2 and a high energy-conversion efficiency of 3.1% were achieved with different compositions of both donor and acceptor materials. The values of V OC is 0.81 V, I SC of 9.6 mA cm − 2 and FF of 40% were observed for the solar cell with the C6PcH2:PC 61 BM composite layer at a weight ratio of 2:1. To improve the FF of the above device, they studied the optimization of the active layer thickness and insertion of buffer layer.…”
Section: Liquid Crystals In Photovoltaics M Kumar and S Kumarmentioning
confidence: 86%
“…The UV-ozone treatment of ITO decreases V OC , whereas it increases on the argon plasma treatment. 121 In 2010, Jeong et al 71 used TP discotics as an additive to well-established P3HT:PC 61 BM BHJ OPV device to realize the effect on PCE. The devices configured with P3HT:PC 61 BM (1:1.2 w-w) layer doped with 2,3,6,7,10,11-hexaacetoxytriphenylene (3 wt%) exhibit an average PCE of 3.97% after thermal annealing.…”
Section: Tp Discotics In Pvsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also investigated the self-assembled supramolecular structures of metal nanoparticles (gold and silver) in the columnar phase of metal free phthalocyanine DLCs [ 66 ]. The results clearly describe the uniform dispersion of NPs in columnar mesophase of phthalocyanine DLCs enhance the electrical conductivity of the nanocomposites up to four orders of magnitude without altering columnar phase.…”
Section: Nanoparticles In Discotic Liquid Crystalsmentioning
confidence: 99%
“…Combining nanomaterials in DLCs has been fast growing current hot research topic in which number of intriguing marvels have been demonstrated and accordingly such DLC-NPs hybrid systems may be useful for various device applications. We initiated this research program by dispersing various functionalized NPs in different DLCs [ 13 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Some aspects of DLC-NP composites are presented here.…”
Section: Introductionmentioning
confidence: 99%